Effects of a Gelled Water on Gastroesophageal Reflux and Gastric Emptying after Percutaneous Endoscopic Gastrostomy - Hiroaki Shigoka; Iruru Maetani; Yuki Yoshida; Kenji Tominaga (Toho Journal of Medicine, 2020)
[ABSTRACT] Introduction: For patients who received percutaneous endoscopic gastrostomy (PEG), semisolid enteral nutrients have recently been utilized with the expectation of reducing the risk of gastroesophageal reflux (GER), which is still controversial. The aim of the present study is to evaluate the GER-preventive effects and gastric emptying of gelled water in post-PEG patients with dysphagia using scintigraphy. Methods: This was a crossover study in which a test using either plain water or gelled water was performed utilizing gastric emptying scintigraphy to investigate the risk of GER and to determine the gastric half-emptying time (T1/2). Results: Radioactivity was detected in the esophageal region, namely GER, in three (12%) patients with plain water, whereas no GER was observed in patients with gelled water (p=0.235). With respect to gastric emptying time, the median T1/2 was longer in patients with gelled water than in those with plain water (31 min vs. 15 min, p<0.0001). Conclusions: Gelled water tends to remain in the stomach for a longer period of time than plain water, leading to a lower risk of GER and rapid gastric emptying. To verify the prevention of aspiration pneumonia and diarrhea, further study with more subjects is warranted.